2006
DOI: 10.1021/jp056915n
|View full text |Cite
|
Sign up to set email alerts
|

Control of the ZnO Nanowires Nucleation Site Using Microfluidic Channels

Abstract: We report on the growth of uniquely shaped ZnO nanowires with high surface area and patterned over large areas by using a poly(dimethylsiloxane) (PDMS) microfluidic channel technique. The synthesis uses first a patterned seed template fabricated by zinc acetate solution flowing though a microfluidic channel and then growth of ZnO nanowire at the seed using thermal chemical vapor deposition on a silicon substrate. Variations the ZnO nanowire by seed pattern formed within the microfluidic channel were also obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 25 publications
(41 reference statements)
0
24
0
Order By: Relevance
“…Furthermore, the ratio of (002)/(100) and (002)/(101) of the samples reduced noticeably with increasing x , reflecting the inhibited growth of ZNR along the c-axis orientation (Table S2). This phenomenon arises mainly from the presence of superfluous OH − that capped on the highest surface energy (002) ZnO Bragg plane during growth process, leading to a randomly oriented nucleation site1415. This finding agrees well with other studies which reported that F − would promote the growth of ZnO crystals along the (101) and (100) plane via occupation of oxygen vacancies (V o ) in ZnO lattice and therefore, hinder the growth of nanorods along (002) plane1617.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the ratio of (002)/(100) and (002)/(101) of the samples reduced noticeably with increasing x , reflecting the inhibited growth of ZNR along the c-axis orientation (Table S2). This phenomenon arises mainly from the presence of superfluous OH − that capped on the highest surface energy (002) ZnO Bragg plane during growth process, leading to a randomly oriented nucleation site1415. This finding agrees well with other studies which reported that F − would promote the growth of ZnO crystals along the (101) and (100) plane via occupation of oxygen vacancies (V o ) in ZnO lattice and therefore, hinder the growth of nanorods along (002) plane1617.…”
Section: Resultsmentioning
confidence: 99%
“…Benefits gained from high-surface-to-volume ratios, as well as electrical or optical confinement in the radial direction, are accessible due to the long lengths of the nanowires, which allow electrical connections and interconnection to be made via conventional lithographic techniques. In the cases where benefits gained from radial confinement are unaffected by nanowire length, nascent techniques have potential for scaling single-nanowire devices to multi-nanowire systems: microfluidic assembly [18, 19], electric field [20, 21], dielectrophoresis [22-24], mechanical transfer [25-27], optical tweezers [28-31], for instance, have potential for aiding in precise placement within smaller-scale systems, while techniques such as Langmuir-Blodgett [32-34], branched nanowire growth [35-37], or 3-D assembly [38, 39] could eventually mature sufficiently for large-scale deterministic system assembly.…”
Section: Introductionmentioning
confidence: 99%
“…We introduce a classical thermodynamics-based model to explain the underlying growth inhibition mechanism via the competitive and face-selective electrostatic adsorption of non-zinc complex ions at alkaline conditions. The performance of these NWs rivals that of vapor-phase-grown nanostructures 56 , and their low-temperature synthesis (<60°C) is favorable to the integration and in-situ fabrication of complex and polymer-supported devices 79 . We illustrate this capability by fabricating an all-inorganic light-emitting diode in a polymeric microfluidic manifold.…”
mentioning
confidence: 99%
“…The self-aligned in-situ synthesis and integration into a functional device eliminates the transfer printing or etching steps typically involved in flexible electronics. Microfluidics-based, surface-adherent synthesis offers a route toward simultaneous spatial patterning of functional materials 9,2930 . As an example, we demonstrate an all-inorganic in-situ fabricated multi-layer light-emitting diode, by sequentially flowing in solution-processable reagents (Fig.…”
mentioning
confidence: 99%